EFEKTIFITAS PENDIDIKAN KESEHATAN DENGAN PENGGUNAAN MEDIA AUDIO VISUAL VIDEO TERHADAP PERUBAHAN PENGETAHUAN REMAJA TENTANG OBESITAS DI SMPN 1 PEKANBARU TAHUN 2019 - Rahmi Pramulia Fitri; Iyang Maisi Fitriani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2019)
Obesity is an increase in the amount of energy that is piled up as a process of increasing fat loss. In 2010 in Riau Province the incidence of obesity was 10.95%. The presence and development of Audio Visual Aid (AVA) media cannot consider the advantages that can provide a more real picture and increase memory retention because it is more interesting and easy to understand. Quantitative research type, quasy experiment method. Research Related to Know About Health Education with Audio Visual Video Media on Changes in Youth Knowledge About Obesity in SMPN 1 Pekanbaru. The study was conducted at SMPN 1 Pekanbaru. The study population was all students in Class 1 and 2 fighting 435 people who were sampled. Sampling technique used (probability sampling). Data collection by questionnaire. Data processing using computerized statistical analysis T Dependent with a degree of confidence 95% p = 0.05. The results of the study showed that before and after health education at SMPN 1 Pekanbaru with AVA media, there were differences in nuanced and more effective knowledge